Improve Learning Outcomes Backhand Service Table Tennis Through Guided Training Method for Class XI Students of SMK Negeri 2 Ambon - Pureng, Haryo; Solissa, J.; Rumahlewang, E. (Peneliti.net, 2024)
This type of research is descriptive research using Classroom Action Research (PTK) with a sample of 18 students taken randomly. Data in this study were taken using test and non-test instruments. Test instruments in the form of observation sheets, affective test sheets, prikomotor and written tests at the end of learning. The results showed that in cycle I students were in failed qualifications with a percentage of 94.44% and sufficient qualifications with a percentage of 5.56%, in cycle II students increased learning outcomes in very good qualifications with a presentation of 55.56% and in good qualifications with a percentage of 44.44%. Thus it can be concluded that there was an increase in learning outcomes after using the guided practice method